2005
DOI: 10.1073/pnas.0505949102
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitinated proliferating cell nuclear antigen activates translesion DNA polymerases η and REV1

Abstract: In response to DNA damage, the Rad6͞Rad18 ubiquitin-conjugating complex monoubiquitinates the replication clamp proliferating cell nuclear antigen (PCNA) at Lys-164. Although ubiquitination of PCNA is recognized as an essential step in initiating postreplication repair, the mechanistic relevance of this modification has remained elusive. Here, we describe a robust in vitro system that ubiquitinates yeast PCNA specifically on Lys-164. Significantly, only those PCNA clamps that are appropriately loaded around ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
255
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(274 citation statements)
references
References 48 publications
16
255
0
3
Order By: Relevance
“…These domains are required by polη and polι (and possibly other Y-family TLS polymerases) for interaction with monoubiquitinated PCNA. Also, in vitro studies have shown that monoubiquitinated PCNA, but not unmodified PCNA, is required for the activation of Rev1 to promote mutagenic DNA replication 13 . Thus, a condition that upregulates PCNA monoubiquitination (such as USP1 knockdown) is likely to increase replication-coupled mutagenesis through the recruitment and activation of multiple TLS polymerases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These domains are required by polη and polι (and possibly other Y-family TLS polymerases) for interaction with monoubiquitinated PCNA. Also, in vitro studies have shown that monoubiquitinated PCNA, but not unmodified PCNA, is required for the activation of Rev1 to promote mutagenic DNA replication 13 . Thus, a condition that upregulates PCNA monoubiquitination (such as USP1 knockdown) is likely to increase replication-coupled mutagenesis through the recruitment and activation of multiple TLS polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a model has emerged in which polη binds to monoubiquitinated PCNA and ensures accurate (error-free) replicative bypass of UV lesions. However, other (error-prone) TLS polymerases (such as polι and Rev1) have recently been shown to rely on monoubiquitinated PCNA for their function 12,13 . How cells limit PCNA monoubiquitination and the unwanted deployment of polη and/or other error-prone TLS polymerases in the absence or presence of extrinsic DNA damage during the synthesis of DNA in S phase is not known.…”
mentioning
confidence: 99%
“…To test for this possibility, we first reconstituted the PCNA monoubiquitylation reaction in vitro using purified Rad6-Rad18. As we and others have shown previously for yeast PCNA (26,27), incubation of human PCNA together with Rad6-Rad18, ubiquitin, ubiquitin-activating enzyme, and ATP but with no DNA, did not support the ubiquitylation of PCNA (Fig. 3B, lane 1), suggesting that PCNA had to be loaded onto DNA for PCNA ubiquitylation.…”
Section: Rad6 -Rad18mentioning
confidence: 77%
“…However when the template contained an abasic site, ubiquitination of PCNA substantially increased the efficiency of TLS by polη and Rev1 [31].…”
Section: Recruitment To the Replication Forkmentioning
confidence: 99%
“…Rev1 interacts with polη, ι, κ and Rev7, in all cases via the same domain contained in its C-terminal 150 aa [32][33][34]. It should also be borne in mind that PCNA is a homotrimer, and the available evidence suggests that ubiquitination is an all or nothing process, ie that all three monomers become ubiquitinated in one trimer [25,31]. Each monomer may therefore be able to interact with a different polymerase, providing a "toolbelt" of different polymerases that can attempt to deal with the blocked fork [35] (Figure 1A).…”
Section: Recruitment To the Replication Forkmentioning
confidence: 99%